Anticancer and Antioxidant Activity of Ethanolic Extract of Markhamia lutea (Benth) K. Schum Stem Bark - Narendran, R.; Ragamanvitha, A.; Arun, K.P.; Brindha, P. (Asian Journal of Chemistry, 2014)
From time immemorial plants have been used to treat various diseases. Drug discovery from medicinal plants has played an important role in the treatment of cancer and, indeed, new clinical applications of plant secondary metabolites and their derivatives have been attempted towards combating cancer. In the present study a Bignoniaceae member, Markhamia lutea (Benth) K. Schum is selected and its chemical as well as anticancer efficacy were studied, with a view to get a lead to develop a safe and efficacious anticancer herbal drug. Ethanolic extract of stem bark of this plant have been prepared and subjected to chemical analysis. Active molecules present in the extract were identified using GCMS and LCMS/MS analysis. Antioxidant activity was assessed using DPPH method. Anticancer activity was evaluated against EAC cells by using MTT assay. The selected plant revealed good antioxidant activity with IC50 value of 169.0 μg/mL and anticancer activity with an IC50 value of 27.0 μg/mL.